FOXA1 Expression in Nasopharyngeal Carcinoma: Association with Clinicopathological Characteristics and EMT Markers. (23rd June 2020) - Ammous-Boukhris, Nihel; Ayadi, Wajdi; Derbel, Mariem; Allaya-Jaafar, Nesrine; Charfi, Slim; Daoud, Jamel; Sellami-Boudawara, Tahya; Mokdad-Gargouri, Raja
Abstract : The forkhead box (FOXA) family of transcription factors regulates gene expression and chromatin structure during tumorigenesis and embryonic development. Until now, the relationship between FOXA1 and the nasopharyngeal carcinoma (NPC) has not yet been reported. Therefore, our purpose is to analyze the expression of FOXA1 in 56 NPC patients compared to 10 normal nasopharyngeal mucosae and to correlate the expression with the clinicopathological features. Besides, we investigated the association between FOXA1 and LMP1 gene expression, as well as the EMT markers namely the E-cadherin and Twist1. Among 56 NPC tissues, 34 (60.7%) cases were positive for FOXA1. Furthermore, we noticed that FOXA1 expression correlated with TNM (p = 0.037 ), and age at diagnosis (p = 0.05 ). Moreover, positive expression of FOXA1 is likely to be associated with prolonged disease-free survival and overall survival rates. On the other hand, we observed a positive association between the expression of E-cadherin and FOXA1 (p = 0.0051 ) whereas Twist1 correlated negatively with FOXA1 (p = 0.004 ). Furthermore, knowing that LMP1 plays a key role in the pathogenesis of NPC, we explored the association of FOXA1 with the LMP1 gene expression in both NPC cell lines and tissues. We found that, in the C666-1 which displays low levels of LMP1, the expression of FOXA1 is high, and inversely in the C15 cell line that expresses a high level of LMP1, the level of FOXA1 is low. Besides, in accordance to our results, we found that in NPC tissues there is a negative association between LMP1 and FOXA1. In conclusion, our results suggest that the overexpression of FOXA1 is associated with a nonaggressive behavior and favorable prognosis in NPC patients. FOXA1 could contribute in the EMT process through key factors as E-cadherin, Twist1, and LMP1.